The sum of our parts: the voices of the Human Genre Project - Boll, Julia (European journal of English studies, 2018)
The Human Genre Project is a website project launched in July 2009, inspired by and in response to the Human Genome Project, which collects writing in very short form. While the project evidently tries to 'humanize and/or translate science for a lay audience', it also attempts to give genetic research, which is often perceived as dehumanised, a 'face'. An attempt to respond to genetic research with a voice that can be identified as the voice of the object (become subject, perhaps) of scientific enquiry, the project counts as an example of the arts reaching out and pointing at the responsibility we have to recognise the Other not as the sum of their parts but as a subject in their own right.